Rethinking Language - Gastor Mapunda; Tracey Costley; Hannah Gibson; Nancy Kula; Colin Reilly (Nordic Journal of African Studies)
The importance of language is consistently ignored within teacher training across Africa, with training designed based on the assumption that learners are fully competent in the medium of instruction (MOI). This causes widespread challenges and often means that children cannot access education in a familiar language. This is particularly true at the primary level, where the familiar languages of the children may not be the same as the specified medium of instruction. Focusing on Tanzania, this paper discusses the need to embed language supportive pedagogies into teacher training at all levels, but particularly at the primary level. The paper discusses interviews with key stakeholders in education which illustrate language attitudes and language use within the classroom. Data from these interviews also highlights the challenges which teachers face relating to language, and the creative methods they use to resolve these challenges. We argue that monolingual approaches to language-in-education are not effective, and that formal training in multilingual, language supportive pedagogies is required to provide teachers with the skills they need to effectively engage with multilingual classrooms. Based on multilingual realities, we make practical suggestions for language supportive pedagogies. We view these pedagogies as an essential factor in teacher training which is linked to wider notions of access and equality, but which is currently being overlooked.